On Transformation Involving Basic Analogue of Multivariable H-Function. (28th May 2020) - Kumar, Dinesh; Ayant, Frédéric; Tariboon, Jessada
Abstract : In this article, fractional order q -integrals and q -derivatives involving a basic analogue of multivariable H -function have been obtained. We give an application concerning the basic analogue of multivariable H -function and q -extension of the Leibniz rule for the fractional q -derivative for a product of two basic functions. We also give the corollary concerning basic analogue of multivariable Meijer's G -function as a particular case of the main result.